Does a single bolus thrombolytic reduce door to needle time in a district general hospital?. Issue 2 (26th February 2004) - Leah, V; Clark, C; Doyle, K; Coats, T J
Abstract : Objectives: To answer the question "In patients presenting with ST elevation acute myocardial infarction (STEMI) and no contraindication to thrombolysis, does the introduction of Tenecteplase reduce door to needle times?" Methods: Firstly, an observational study was performed to compare the time taken to prepare standard thrombolytic therapy with Tenecteplase. Secondly, door to needle times were compared before and after the introduction of Tenecteplase. The study was powered to be 80% sure of finding a change of 10% in the number of patients meeting the national service framework standard of a 30 minute door to needle time. Results: Tenecteplase takes 10.5 minutes less time to prepare than standard treatment (p value <0.001). After the introduction of Tenecteplase the percentage of patients receiving thrombolysis in 30 minutes increased from 58% to 76% (p value <0.01) Conclusion: Tenecteplase is quicker to prepare than standard therapy, resulting in a significant improvement in performance against the national service framework target.